answer
m = 5/6
how ❓
When doing math problems, you want to consider...
- First step
- Understand concept
- Why your answer is your answer
To make sure we get to those 3 topics, we will do the long equation.
discuss topics
- Part 1 is simplifying
- Part 2 is grouping the left side
- Part 3 is grouping right side constants
- Part 4 is isolating m
_______________________________________________________
solve (part 1)
![4\cdot \left(\frac{\mathrm{m}}{4}+(2)/(4)\right)=5\cdot \mathrm{m}+(-4)/(3)\\](https://img.qammunity.org/2023/formulas/mathematics/high-school/hflq8n7376m7rbbcj657gox9k4lyenadpz.png)
![4\cdot \left(\frac{\mathrm{m}}{4}+(2)/(4)\right)=5\cdot \mathrm{m}+(-4)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/ly6k11rl4lk4s3vhsfbik5iwsj198dmhw6.png)
![4\cdot \left(\frac{\mathrm{m}}{4}+(\left(1\cdot 2\right))/(\left(2\cdot 2\right))\right)=5\cdot \mathrm{m}+(-4)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/olx4pvhy88775uy2qa1f0qlycl9g32bglf.png)
![4\cdot \left(\frac{\mathrm{m}}{4}+(1)/(2)\right)=5\cdot \mathrm{m}+(-4)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/tu7nku838imx5jwmthaj055yj2ebmcw5c1.png)
![\frac{\left(\mathrm{m}\cdot 4\right)}{4}+(\left(1\cdot 4\right))/(2)=5\cdot \mathrm{m}+(-4)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/cnhvv2tjavqz8f4xycctp9a8iletw2nlfq.png)
![\frac{\left(\mathrm{m}\cdot 4\right)}{4}+(4)/(2)=5\cdot \mathrm{m}+(-4)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/ql995ghj4sb2okrcttb9xssm7c6wlpltag.png)
![\mathrm{m}+(4)/(2)=5\cdot \mathrm{m}+(-4)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/4m0749fv92xf6n3twlz95wdrioqs4vgx4z.png)
![\mathrm{m}+(\left(2\cdot 2\right))/(\left(1\cdot 2\right))=5\cdot \mathrm{m}+(-4)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/mbjyum4dzqmmti7s3txc0g3r6c7ywejzp8.png)
![\mathrm{m}+2=5\cdot \mathrm{m}+(-4)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/q7avfaixmj0il42e7j296un839r8k14t72.png)
solve (part 2)
![\mathrm{m}+2=5\cdot \mathrm{m}+(-4)/(3)\\\mathrm{m}+2-5\cdot \mathrm{m}=5\mathrm{m}+(-4)/(3)-5\cdot \mathrm{m}\\\mathrm{m}-5\cdot \mathrm{m}+2=5\cdot \mathrm{m}+(-4)/(3)-5\cdot \mathrm{m}\\-4\cdot \mathrm{m}+2=5\cdot \mathrm{m}+(-4)/(3)-5\cdot \mathrm{m}\\-4\cdot \mathrm{m}+2=5\cdot \mathrm{m}-5\cdot \mathrm{m}+(-4)/(3)\\-4\cdot \mathrm{m}+2=(-4)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/nvyfvlqvxdgmumbmrafwnb2who2elvr8rc.png)
solve (part 3)
![-4\cdot \mathrm{m}+2=(-4)/(3)\\-4\mathrm{m}+2-2=(-4)/(3)-2\\-4\cdot \mathrm{m}=(-4)/(3)-2\\-4\cdot \mathrm{m}=(-4)/(3)+(-6)/(3)\\-4\cdot \mathrm{m}=(-4-6)/(3)\\\\-4\cdot \mathrm{m}=(-10)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/pn3lf5qnqajsabfdra8uday2l94t1w9gy0.png)
solve (part 4)
![-4\cdot \mathrm{m}=(-10)/(3)\\\frac{-4\mathrm{m}}{-4}=((-10)/(3))/(-4)\\\frac{4\cdot \mathrm{m}}{4}=((-10)/(3))/(-4)\\\mathrm{m}=((-10)/(3))/(-4)\\\mathrm{m}=(-10)/(3\cdot -4)\\\\\mathrm{m}=(5)/(6)](https://img.qammunity.org/2023/formulas/mathematics/high-school/pxawzt9xdylxumbn29erhiognsw1lw9t3w.png)